Prevalence and associated predictors of HIV and syphilis among women, south of Brazil (Research, Society and Development, 2021)
To investigate the general prevalence of sexually transmitted infections (STIs) and the factors associated with syphilis and HIV in women treated in the Integrated Health System (SINAS). Cross-sectional database study with 6.993 patients treated at a referral center in the state of Paraná, Brazil, from January 2013 to December 2015. The overall prevalence was 2.39% for syphilis and HIV, being 0.65 and 0.22% for pregnant women and 3.07 and 0.78% for non-pregnant women, respectively. After adjusting the variables in the logistic regression model, the main predictors associated with syphilis were the age groups 41 to 59 and 60 to 83 years old (p